Epidemic of Modern Era - Polycystic Ovary Syndrome (PCOS) with Scientific Burden (Homoeopathy for All, 2023)
Polycystic ovary syndrome (PCOS)  is a new gynecological epidemic. It is  the most common endocrine disorder  among women of reproductive age  groups 12-45 years. It is thought  to be one of the leading causes  of female subfertility and the most  frequent endocrine problem in women  of reproductive age. This article  provides an overview of the aetiology,  diagnosis, and appropriate general &  homoeopathic management of PCOS.
Keywords: gynecological; women